New Light on Central Asia - Ahmad Hasan Dani (Lahore Sang-e-Meel Publications, 1996)
Collection of articles previously published in various magazines and newspapers of Pakistan, during 1985 and 1992.
Include Index.
Keywords: Asia, Central -- Soviet Union--Former Soviet Republics